2021
DOI: 10.3390/healthcare9121628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cycle-Based High-Intensity Interval Training and Moderate to Moderate-Intensity Continuous Training in Adolescent Soccer Players

Abstract: Cardiorespiratory fitness, anaerobic power, and lower extremity strength are essential for soccer players at all levels. An effective program should be developed to improve physical strength for adolescent soccer players who need to combine academic and technical training. This study analyzed the impact of short-term high intensity interval training (HIIT) training and traditional moderate intensity continuous training (MICT) on adolescent soccer players. Participants included 56 adolescent soccer players who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…From the aspect of kinesiological analysis, football (soccer) is a contact sport of intermittent and poly-structural nature, with high technical-tactical and physical demands [ 1 , 2 , 3 ]. Each player’s performance is directly influenced by the environment (i.e., teammates, opponents, and ball).…”
Section: Introductionmentioning
confidence: 99%
“…From the aspect of kinesiological analysis, football (soccer) is a contact sport of intermittent and poly-structural nature, with high technical-tactical and physical demands [ 1 , 2 , 3 ]. Each player’s performance is directly influenced by the environment (i.e., teammates, opponents, and ball).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that high-intensity interval training can improve soccer players' aerobic and anaerobic abilities (Arazi et al, 2017;Fang et al, 2021). In practice, highintensity interval training induces more excellent glycolytic activity in a short time, resulting in the production of lactic acid, and this activity beneficially contributes to producing higher levels of ATP (Stöggl & Björklund, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…A YYIR1 and a laboratory exercise test (Bruce protocol) were chosen based on Fang et al's research ( 47 )—were also performed on the athletes to assess accurate physiological characteristics and to determine the expected maximum heart rate (HRmax) and estimated aerobic capacity (VO2max) ( 48 ): 0.0084 36.4 …”
Section: Methodsmentioning
confidence: 99%